Hybrid Nanofluid Flow and Heat Transfer Past a Vertical Cylinder in the Presence of MHD and Heat Generation - Rajesh, V.; Sowjanya, G. Bala; Chamkha, Ali (Communications in Mathematics and Applications, 2022)
The basic objective of this work is to investigate the effects of Lorentz force and internal heat generation on the unsteady flow of a hybrid nanofluid and the heat transfer caused by a moving semi-infinite vertical cylinder. The governing partial differential equations are solved numerically using a robust implicit finite difference approach with proper boundary conditions. The current work is corroborated by existing literature on the subject of special situations of the problem. The effects of the magnetic parameter, the Grashof number, and the heat generation parameter on the Nusselt number, the skin friction coefficient, as well as the velocity and temperature fields, have been investigated and graphed. The results obtained can be applied to a variety of engineering devices, such as chemical reactors, heat exchangers, and solar collectors.
Keywords: Free convection; Vertical cylinder; Hybrid nanofluid; MHD; Heat generation; Finite difference numerical method